Safety and efficacy of a novel three-dimensional printed microporous titanium prosthesis for total wrist arthroplasty in the treatment of end-stage wrist arthritis - Cai, Xingbo; Wang, Bin; Zhang, Bihuan; Zhang, Yue; Wang, Teng; Lin, Wei; Huang, Youjun; Chen, Bingquan; Zhou, Siyuan; Lu, Sheng; Xu, Yongqing (Frontiers in Bioengineering and Biotechnology, 2023)
Background: Total wrist arthroplasty is an effective treatment for end-stage wrist arthritis from all causes. However, wrist prostheses are still prone to complications such as prosthesis loosening and periprosthetic fractures after total wrist arthroplasty. This may be due to the wrist prosthesis imprecise matching with patient's bone. In this study, we designed and developed a personalized three-dimensional printed microporous titanium artificial wrist prosthesis (3DMT-Wrist) for the treatment of end-stage wrist joint, and investigated its safety and effectiveness. Methods: Total wrist arthroplasty was performed using 3DMT-Wrist in 14 cases of arthritis between February 2019 and December 2021. Preoperative and postoperative visual analog scale scores, QuickDASH scores, wrist range of motion, and wrist grip strength were evaluated. Data were statistically analyzed using the paired samples t-test. Results: After 19.7±10.7 months of follow-up, visual analog scale decreased from 66.3±8.9 to 6.7±4.4, QuickDASH scores decreased from 47.4±7.3 to 28.2±7.6, grip strength increased from 5.6±1.4 kg to 17.0±3.3 kg. The range of motion improved significantly in palmar flexion (30.1±4.9° to 44.9±6.5°), dorsal extension (15.7±3.9° to 25.8±3.3°), ulnar deviation (12.2±3.9° to 20.2±4.3°) and radial deviation (8.2±2.3° to 16.2±3.1). No dislocation or loosening of the prosthetic wrist joint was observed. Conclusion: Total wrist arthroplasty using 3DMT-Wrist is a safe and effective new treatment for various types of end-stage wrist arthritis; it offers excellent pain relief and maintains the range of motion.